Aesthetic rehabilitation of posterior teeth with direct composite restorations (a case report) - A. Mitronin; D. Ostanina; A. Ruzina; O. Khvorostenko (Эндодонтия Today)
Aesthetic composite restoration is the most common method for dental hard tissue defects reconstruction. Despite the active development and use of ceramic restorations for dental rehabilitation, the introduction of new nanotechnological filling materials has opened up fundamentally new possibilities in restorative dentistry. This article represents a clinical case of direct composite restoration in teeth 25, 26 and 27 using new nanoceramic materials.